Identify the Role of Students to Implement Sustainable Development Goals (SDGS) 4.4 - Edo Mashanriza Landaoe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research originated from the UN (United Nations) conference which discussed and established the 2030 Sustainable Development Goals (SDGs). Indonesia is known to also support the 2030 Sustainable Development Goals (SDGs) program by (SDGs) 2030 with the National Long-Term Development Plan and National Medium Term Development Plan. SDGs have become a measuring tool in determining Impact Ranking. Academics are stakeholders who play a role in helping the achievement of SDGs, especially SDGs 4.4 in this study. This study aims to identify the role of students in the Telkom University campus within the Faculty of Business Communication. This study used a quantitative methodological approach, where the data obtained were analyzed using quantitative descriptive analysis methods through the continuum line, chi-square test and t-test differences.  The results of this study provide information that there are 129 (68.61) FKB students who do not yet know what the Sustainable Development Goals (SDGs) are, then the results show that SDGs 4 and SDGs 8 get the first priority. and secondly in student perception. Based on the results of the chi-square test, it was found that 7 of the 42 indicators of this study were statistically stated to have a relationship with the type of student faculty. Next, based on the results of the different t-test, it was found that there were 11 out of 42 research indicators that were different or not the same among the types of student faculties..